Genocide against the Indians : its role in the rise of US capitalism - Novack, George (New York : Pathfinder Press, 1972)
Bibliotheek François Vercammen
Bevat : The Conquest of the indians , The Destruction of Indian Communal Democracy , The Indians and the Struggle for Possession of the Land
Deze 3 artikels zijn het eerst verschenen in januari, april en mei 1949, thema van de Vierde Internationale. Later werden zij verzameld in het boek 'Marxist Essays in American History (Merrit Publshers, 1966)
Engels
Brochure